2018
DOI: 10.1021/acs.langmuir.7b04255
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Multiarm Copolymers with a UCST Phase Transition: Topological Effect and the Mechanism

Abstract: A novel thermoresponsive hyperbranched multiarm copolymer with a hydrophobic hyperbranched poly[3-ethyl-3-(hydroxymethyl)oxetane] core and many poly(acrylamide- co-acrylonitrile) (P(AAm- co-AN)) arms was for the first time synthesized through a reversible addition-fragmentation chain-transfer polymerization. These copolymers show reversible, sharp, and controlled temperature-responsive phase transitions at the upper critical solution temperature (UCST) in water and electrolyte solution. It is the first report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 40 publications
1
31
1
Order By: Relevance
“…RAFT polymerization was then performed using Aam and AN as monomer, AIBN as initiator and HBPO-DTBA as RAFT agent (Figure 7). In contrast to the report of Asadujjaman et al [34], the UCST of this novel hyperbranched polymer can be increased by decreasing the arm (chain) length due to its unique molecular topology [39]. Synthesis of an ABA type triblock copolymers using P(AAm-co-AN) as outer blocks or middle block and hydrophilic poly(poly(ethylene glycol) methyl ether methacrylate) (PPEGMMA) and poly (N,N-dimethylacrylamide-co-7-acryloyl-4-methylcoumarin) as middle block and outer block, respectively, have also been reported [40,41].…”
Section: Poly(acrylamide-co-acrylonitrile)contrasting
confidence: 68%
See 2 more Smart Citations
“…RAFT polymerization was then performed using Aam and AN as monomer, AIBN as initiator and HBPO-DTBA as RAFT agent (Figure 7). In contrast to the report of Asadujjaman et al [34], the UCST of this novel hyperbranched polymer can be increased by decreasing the arm (chain) length due to its unique molecular topology [39]. Synthesis of an ABA type triblock copolymers using P(AAm-co-AN) as outer blocks or middle block and hydrophilic poly(poly(ethylene glycol) methyl ether methacrylate) (PPEGMMA) and poly (N,N-dimethylacrylamide-co-7-acryloyl-4-methylcoumarin) as middle block and outer block, respectively, have also been reported [40,41].…”
Section: Poly(acrylamide-co-acrylonitrile)contrasting
confidence: 68%
“…Copolymerization of P(AAm-co-AN) with PVP was also explored in order to generate a LbL temperature-responsive films, which assembled in well-defined block copolymer micelles below UCST [38]. Qi et al [39] reported synthesis of first hyperbranched UCST polymer using poly [3-ethyl-3-(hydroxymethyl) oxetane] (HBPO) as core and P(AAm-co-AN) as arm. Hydroxyl end groups of HBPO was first converted into carboxylic acid by attaching maleic anhydride followed by generation of RAFT agent HBPO-DTBA (poly[3-ethyl-3-(hydroxymethyl)oxetane]-dithiobenzoic acid).…”
Section: Poly(acrylamide-co-acrylonitrile)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, by copolymerizing with hydrophobic polymers, the UCST AAm‐based copolymer can be obtained. It is important to note that copolymers of AAm and non‐polar vinyl monomer such as poly(acrylamide‐ co ‐acrylonitrile) [ 19,28–33 ] and poly(acrylamide‐ co ‐styrene) [ 34 ] were reported to display the UCST behavior in water. Upon cooling below UCST, its primary amide groups which are responsible for the thermally reversible hydrogen bonding tend to be switched from the interaction with water to intramolecular formation leading to self‐aggregation and phase separation from water molecules.…”
Section: Methodsmentioning
confidence: 99%
“…A similar approach was used for preparation of hyperbranched copolymers with AM and acrylonitrile. 41 Wang et al 14,15 synthesized hyperbranched PAMs using a semi-batch strategy by controlling crosslinker addition. The PAM-based nanogels were obtained via a RAFT dispersion polymerization.…”
Section: Introductionmentioning
confidence: 99%